The Cigarette Smoking Knowledge and Attitude Components of Adolescence in Muhammadiyah Junior High School of Jakarta - Fatin Najwa; Nurdiyana Abdul Manap; Ahmad Syazrain; Muhamad Izzuddin; Tria Astika Endah Permatasari; Siti Riptifah Tri Handari (Jurnal Kedokteran dan Kesehatan, 2014)
The World Health Organization (WHO) attributes more than 4 million deaths per year due to tobacco, and it is expected that this figure will rise to 10 million deaths per year by 2020. Moreover, it is now a growing public health problem in developing world. To investigate the knowledge and attitude component of adolescence in Madrasah TsanawiyyahMuhammadiyah Indonesia about cigarette smoking. Across sectional study was conducted using self administered questionnaire among 97 students of Madrasah Tsanawiyyah Muhammadiyah which has 2 components which are knowledge and attitude. Non probability sampling was used in selection of the respondents. Majority 78% of the respondent obtained a good rating for their knowledge component and about 79% obtained a good rating obtained a good rating for attitude. The smoke-free could reduce both the acceptability (norms) and availability of tobacco to youth.